Agropastoral herding practices and the grazing behaviour of cattle - Bayer, W. (International Livestock Centre for Africa, 1986)
Presents results of a study of grazing behaviour and forage resources utilisation by herded cattle belonging to agropastoralists at Abet & Kurmin Biri in the subhumid zone of Nigeria as well time spent on walking, resting & watering. Subdivides grazing activities into natural range grazing, browsing, grazing of crop residues and of burnt areas.